PROFIL GURU PROFESIONAL BERDASARKAN PERSEPSI MAHASISWA CALON GURU - Sudarisman, Suciati (Universitas Sebelas Maret, 2014)
The purpose of this study was to determine the teacher candidatesâ€™ perception about professional teacher profile as stated in the Indonesian Teacher Regulation (2005). This research an descritive qualitative were involved 62 teacher candidates of Mathematics and Science Education Department, Faculty of Teacher Training and Education, Sebelas Maret University as respondents. The data was collected with non-test techniques by questioner. Data analyzed by descriptive qualitative approach and served in diagram. The results showed: there are 95,24% teacher candidates have uncorrect perception and just only 4,76% students have correct perception about the profile of professional teacher. Based on the result of the research can be concluded that mosly teacher candidates have uncorrect perceptions about the profile of professional teacher. As effort to build the professional teacher for future, can be suggested that teacher candidates have to get correct concept about professional teacher especially through education profession matterial.Â Keywords: teacher candidatesâ€™ perception, the profile of professional teacher